Investigation of the gamma shielding efficiency reduction by depositing PbO and MnO2 composition on various types of substrates - Alhamdi Walat Abdulqader; Khalil Mohammed Hussein (Nuclear Technology and Radiation Protection, 2023)
In this study, a PbO, MnO2, PbO + MnO2 thin film (nano layer) was deposited onto a microscope glass, indium tin oxide glass, and aluminum with thicknesses 0.1 mm and 0.5 mm substrate, samples were prepared by the thermal spray technique. The coating of thin films was carried out onto the substrate at a temperature of 35°C, furthermore, the prepared shield films were annealed at 100°C and 250°C for one hour. The shielding efficiency of each thin film on each substrate at different temperatures was analyzed using radioactive source 60Co and NaI(Tl) well-type scintillation detector. The experimental results obtained were summarized: adding PbO or MnO2 thin film together or separately to the substrate increases the attenuation of gamma-rays depending on the type of samples and annealed temperature. The minimum gamma reduction rate was found 0.3 % for indium tin oxide glass deposited with MnO2 and annealed at 250°C while the maximum was found in Al with thickness 0.1 mm (9.6 %) deposited with both PbO or MnO 2 together. This means that shielding efficiency increases by increasing the thickness of the thin film, annealed temperature and substrate type.